Priority directions of geological exploration for oil and gas in the northeastern part of the Black Sea - N.I. Evdoshchuk; T. Galko; T. Dovzhok; O. Sedlerova (Геофизический журнал, 2013)
The first oil field in the water areas of Ukraine was discovered by drilling in 2004—2006 on the Subbotina structure within the northeastern part of the Black Sea in the Ukrainian sector of the Kerch continental shelf in the KerchTaman depression in lower Maikop sediments. For rapid development of new oil and gas Subbotina region exploration has to be conducted in Maikop complex, the search in sediments overlaying the Maikop series, parametric drilling with detailed seismic surveys and a set of nontraditional methods of prospecting in rock complex lying under the Maikop.